An Institutional Evaluation of the CSR Competency Framework: Developing CSR Skills and the Role of Business Education - Dlamini, Nelisiwe (2005)
The UK Government has encouraged the adoption of CSR principles through various measures outlined in this paper. For organisations, the decision to adopt and implement CSR, however, presents various practical issues. As pressure from different sources mounts, organisations are turning to the market for skilled and knowledgeable people. This is, however, problematic because CSR is an emerging and dynamic field that responds to national and organisational circumstances. Historically, CSR practitioners have been drawn from various functional and professional backgrounds.